2022
DOI: 10.17305/bjbms.2021.7082
|View full text |Cite
|
Sign up to set email alerts
|

Strategies and safety considerations of booster vaccination in COVID-19

Abstract: First-generation SARS-CoV-2 vaccines have played a significant role in controlling the COVID-19 pandemic, preventing severe diseases, and reducing mortality. However, the continuous emergence of SARS-CoV-2 variants, the persistence of breakthrough infections, and the seemingly rapid decline in the protective efficacy of SARS-CoV-2 vaccines have presented additional challenges for the next phase. There is an urgent need to confirm the necessity of further booster vaccination and combination vaccine approaches. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 86 publications
0
7
0
Order By: Relevance
“…However, the best strategies and dosing intervals to provide maximum benefit, especially in the context of the new variants spread, still need to be clearly defined [ 63 ]. Similarly, although many policies define priority groups to administer vaccines as reported in our results, a systematic review concluded that the current evidence on prioritization is still insufficient and there is need of adequately powered research assessing this issue [ 65 , 66 ].…”
Section: Discussionmentioning
confidence: 90%
“…However, the best strategies and dosing intervals to provide maximum benefit, especially in the context of the new variants spread, still need to be clearly defined [ 63 ]. Similarly, although many policies define priority groups to administer vaccines as reported in our results, a systematic review concluded that the current evidence on prioritization is still insufficient and there is need of adequately powered research assessing this issue [ 65 , 66 ].…”
Section: Discussionmentioning
confidence: 90%
“…Severe acute respiratory syndrome coronavirus 2 is a severe infectious respiratory virus that causes COVID‐19 and damages almost all human organs, including the lungs, heart, kidneys, liver, and brain, even leading to death in severe cases. 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 To contain the sudden COVID‐19 epidemic, almost all countries in the world have not only recommended that their citizens be vaccinated against COVID‐19 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 but also adopted a series of strict NPIs, such as hand hygiene, use of face masks, social distance, limiting mass gatherings, school closures, and staying at home orders. NPIs disrupt the transmission chain of respiratory diseases, so they are equally effective in controlling other respiratory virus infections.…”
Section: Discussionmentioning
confidence: 99%
“…As the experiment showed, a booster dose of vaccine can increase the titer of neutralizing antibodies. "The results showed that the neutralizing antibody titers increased from 440AU/mL to 25,468 AU/mL after the booster dose, and no serious adverse events were reported during this period" [4].…”
Section: Traditional Vaccinementioning
confidence: 94%
“…Homologous inoculation refers to injecting the same type of vaccine as a booster. In contrast, heterologous vaccination refers to a "combination of vaccines from different manufacturers or different techniques routes" [4]. Homologous inoculation, injecting the same vaccine and triggering the second immune response, elicit rapid and intense secretion and maturity of antibodies, resulting in longer protection effectiveness.…”
Section: Traditional Vaccinementioning
confidence: 99%